THE INFLUENCE OF EDUCATION, NUMBER OF DEPENDENTS AND INCOME TO THE AMOUNT OF SAVING ON THE COOPERATIVE CREDIT UNION BANURI HARAPAN KITA IN THE DISTRICT OF BALAI BATANG TARANG - B01111111, Dwi Apriana Elisa Apriana Elisa (Jurnal Curvanomic, 2016)
This thesis entitled â€œThe Influence of Education, Number of Dependents and Incometo the Amount of Savings on the Cooperative Credit Union Banuri Harapan Kita in theDistrict of Balai Batang Tarangâ€ this study aims to analyze the influence of education,number of dependents and income to the amount of savings on the Cooperative Credit UnionBanuri Harapan Kita. The method used is descriptive form of research used data analysisClassical Test assumptions in linear regression analysis and test statistics, the sample used inthis study were 50 respondents.Results of the analysis showed that (1) education is not significant negative effect onthe amount of savings (2) the number of dependents is not significantly negative effect on theamount of savings (3) revenues significantly and positive influence on the amount of savings,there is the influence of education, number of dependents and income simultaneously to theamount of savings in the Cooperative Credit Union Banuri Harapan Kita in the district ofBalai Batang Tarang.From the analysis of the data in this study showed that all three factors: education,number of dependents and income can be accounted for 38.0% of total savings in theCooperative Credit Union Banuri Harapan Kita in the district of Balai Batang Tarang, whilethe remaining 62.0% influenced by other factors such as service, the requirements /procedures, facilities and location of the location. Where the other factors that most affect theinterest of saving money are the requirements / procedures.Keywords: education, number of dependents, income, other factors and savings